Needs Analysis of Project Based Learning Learning Model Development in Translation as Profession Course - Siregar, Masitowarni (BIRCU, 2021)
This study aims to analyze the need for developing a project based learning model for students of the Translation as Profession Course at the English Education Study Program, F This research is a qualitative descriptive research aimed at identifying the needs, opinions and suggestions of the respondents to be used as material for the development of learning models. The instruments used to collect data are questionnaires and interviews. The results of questionnaires and interviews with lecturers state that lecturers need a learning model that can maximize students' learning to translate, lecturers also stated that they needed a learning model guide with clear activity guidelines and accurate assessment guidelines. Students also stated that they needed a learning model that could maximize their translation skills, a learning model that could solve the translation problems they found and a learning model that could maximally motivate students to work in groups.